Urinary NGAL as an Early Marker of Renal Dysfunction in Dogs with Heartworm Disease and Pulmonary Hypertension - Noelia Costa-Rodríguez; Daniel Julio Vera-Rodríguez; Soraya Falcón-Cordón; Beatriz Regina Morales; Rodrigo Morchón; José Alberto Montoya-Alonso; Elena Carretón (Animals)
Heartworm disease, caused by Dirofilaria immitis, often leads to pulmonary hypertension (PH), a serious cardiovascular complication in infected dogs. PH may impair renal function through hemodynamic and inflammatory mechanisms, even when traditional biomarkers such as serum creatinine and blood urea nitrogen (BUN) remain within normal ranges. This study aimed to assess urinary neutrophil gelatinase-associated lipocalin (uNGAL) levels in dogs naturally infected with D. immitis, with and without PH, to evaluate its potential as an early biomarker of renal dysfunction. Forty-two infected dogs were included and divided into two groups based on the presence (n = 14) or absence (n = 28) of PH, diagnosed via echocardiography. uNGAL concentrations were significantly higher in dogs with PH (mean 66.49 ± 6.67 ng/mL) compared to those without PH (mean 49.01 ± 14.48 ng/mL; p < 0.0001), despite normal creatinine and BUN values. No significant associations were found between uNGAL and sex, age, breed, or clinical signs. These findings suggest that uNGAL may serve as a sensitive biomarker of early renal impairment in dogs with heartworm disease and PH, even in the absence of overt azotemia, supporting its use in clinical evaluation and the monitoring of disease progression.